Pengaruh Artificial Intelligence (AI) terhadap Digital Literasi Mahasiswa Ilmu Perpustakaan Angkatan 2021 UIN Sumatera Utara, Medan - Tamara Oktafiani Zega; Abdul Karim Batubara (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Artificial Intelligence (AI) is a technology in the Society 5.0 era which is very useful for application in the world of education, especially Library Science. Artificial Intelligence (AI) is an artificial intelligence that is a model of human intelligence that has been applied in a machine to create intelligent machines that are able to facilitate information activities. There is increasing recognition of the benefits of applying Artificial Intelligence (AI) to the world of education. This research explores how Artificial Intelligence (AI) in the world of education for Library Science students is able to respond to opportunities and improve major strategies to obtain more information on digital literacy. The data in this research was obtained using quantitative methods by taking 45 students majoring in Library Science, UIN North Sumatra, Medan as samples and conducting a literature review of research related to the discussion being researched. It is very rarely mentioned explicitly that artificial intelligence used by library science students is able to provide a huge boost to ideas, creativity, literacy character which is able to encourage the growth of good information for each individual. This research is a discussion that explores the meaning, benefits and challenges of Artificial Intelligence (AI) on the digital literacy of library science students at UIN North Sumatra, Medan.